Aqueous near infrared fluorescent composites based on apoferritin-encapsulated PbS quantum dots - Hennequin, Barbara (2008)
Quantum dots offer a number of advantages over standard fluorescent dyes for monitoring biological systems including high luminescence, stability against photobleaching, and a wide range of fluorescence wavelengths from blue to infrared depending on the particle size. In this work, we investigated in using the protein cage apoferritin as a template for the synthesis of colloidal quantum dots.